Thermal conversion and epitaxial overgrowth of nanopores etched in InP and GaAs. (7th May 2012) - Nohavica, D.; Grym, J.; Gladkov, P.; Hulicius, E.; Pangrác, J.; Jarchovský, Z.
Both crystallographically oriented and current line oriented pore networks in InP and GaAs are created by electrochemical dissolution. Heat treatment of InP pores at 650°C and of GaAs pores at 700–850°C converts them into microcavities maintaining almost the same crystallographic direction. As a transition between micro/nanopores and micro cavities the lamellar structures are obtained. Mass transport is responsible for the pore conversion. The effect of 'anion' vapour pressure is proved to be crucial for the microcavity formation since it influences the mass transport during the heat treatment. Electron microscopy and photoluminescence experiments reveal the absence of significant extended defects, both after the formation of pores and cavities. The capability of improved structural quality of homo– and hetero–epitaxially overgrown films on porous InP is demonstrated by liquid phase epitaxy growth of InP and InAs. Overgrowth of the porous GaAs substrates by ternary GaInAs layers with different lattice mismatch was realised by metal organic vapour phase epitaxy.